PENANAMAN NILA-NILAI ISLAMI SESUAI KULTUR SEKOLAH PADA SISWA DI MI RADEN FATAH SUKUN - Ita Diana Sari; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Islamic values are values based on Islamic provisions. Instilling Islamic values in students is expected to become better individuals by having good morals, so that they can become useful role models for others and their environment. Aspects of Islamic values consist of 3 things, namely the value of aqidah, moral values, and worship values. This study discusses the process of instilling Islamic values in accordance with school culture, the efforts made in the process of instilling Islamic values, and also the factors that influence the inculcation of Islamic values according to school culture at MI Raden Fatah Sukun. This type of research is a qualitative research with descriptive method. From the results of this study indicate that: The school at MI Raden Fatah Sukun can be said to be quite good. this can be seen in terms of attitudes, worship and muamalah fellow students. The culture at MI Raden Fatah is reading prayers before lessons, reading 3 letters before lessons, praying the midday prayer in congregation, reading and writing the Qur'an (BTA), commemorating Islamic holidays, and jariyah. become a reference for schools to instill good Islamic values for students.Keyword: Islamic Values, Students, School Culture